Nanomole Process: Enabling Localized Metallic Back-Gates for Enhanced Cryogenic Front-to-Back Coupling in FDSOI Quantum Dots - Fabio Bersano; Niccolo Martinolli; Ilan Bouquet; Michele Ghini; Eloi Collette; Liza Zaper; Floris Braakman; Martino Poggio; Mathieu Luisier; Adrian Mihai Ionescu (IEEE Journal of the Electron Devices Society)
This paper introduces a novel integration method of localized metallic back-gates into fully-depleted silicon-on-insulator (FDSOI) multi-gate FETs, enabling robust front-to-back electrostatic coupling from room temperature to cryogenic conditions, without the need for substrate implantation. The fabrication process, termed the Nanomole process, utilizes nanometric vapor-phase etching of the buried oxide or silicon substrate with vapor-HF and XeF2 gases. This is followed by atomic layer deposition (ALD) of a dielectric material and Pt, with precise patterning achieved through inductively coupled plasma etching. Detailed analysis of the process demonstrates controllable etch rates based on device geometry, providing calibrated guidelines for scalable manufacturing. Symmetric mid-k dual-gating is reported in devices featuring a Si-film thickness of 24 nm, with a top and bottom gate oxide equivalent thickness (EOT) of 6.5 nm. Electrical characterization of multi-gate FDSOI SETs, operated as FETs, confirms effective threshold voltage tuning through dual-gate operation, with consistent performance from room temperature to millikelvin regimes. Additionally, quantum mechanical simulations based on the effective mass approximation at 4 K offer insights into the electrostatic behavior of dual-gated SOI quantum dot devices in both planar and nanowire geometries. This scalable and versatile technological solution opens new possibilities for advanced quantum devices, such as charge and spin qubits, by enabling in situ control over volume inversion, electron valley splitting, and spin-orbit interaction.